CUSTOMER EXPERIENCE AS AN IMPORTANT FACTOR IN EVALUATING TELECOMMUNICATIONS SERVICES - Dijana Vuković; Ana Globočnik Žunac; Boris Jurič (International Journal for Quality Research, 2023)
The swiftness of approaching the customer and response to customer requests are becoming key parameters in the business of telecommunications companies. Here the focus of interest is placed on recognizing and then meeting customer needs in the shortest possible time. Telecommunication companies respond to the demands of the competitive market by independently strengthening their position through increasing market share, acquiring or merging competing companies, and continuously developing telecommunications products and services. Changes in the role of telecom operators, growth and strengthening of the economy, changes in regulation and the role of regulators change telecommunications services. This allows telecommunications companies to calculate the revenue structure, which forces them to offer a more diverse range of services, respond faster to demand and compete on price. The reputation of telecommunications companies is becoming increasingly important in both domestic and international presentations.